Preparation method and application of optical gain flexible thermoelectric ionic gel

By introducing AuNPs@SiO2 into eutectic solvent ion gel and multiplying the Seebeck coefficient under specific band irradiation, the problem of single function and poor mechanical properties of the existing eutectic ion gel is solved, and high Performance flexible thermoelectric materials.

CN119463014APending Publication Date: 2025-02-18JIANGNAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411360421.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing eutectic ion gel has a single function, poor mechanical properties, and precious metal nanoparticles cannot effectively improve the thermoelectric conversion rate under specific wavelength light.

Method used

By introducing AuNPs@SiO2 into the PAA-Zn-DES ion gel, the Seebeck coefficient multiplication effect is achieved under specific band irradiation. The process includes preparing a mixture of eutectic solvent and anhydrous zinc chloride and homogeneously mixing and polymerization curing with acrylic acid, AuNPs@SiO2 and photoinitiator under UV conditions.

Benefits of technology

The Seebeck coefficient is doubled, the thermoelectric and mechanical properties of the gel are improved, and the characteristics of good flexibility, high transparency, self-repair ability and green environmental protection are good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463014A_ABST
    Figure CN119463014A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of optical gain flexible thermoelectric ionic gel, and the method comprises the steps: introducing AuNPs coated SiO2 into PAA-Zn-DES ionic gel, and achieving the effect of Seebeck coefficient multiplication under the irradiation of a specific wave band. The main reason of multiple enhancement of the effect is that free electrons on the surface oscillate collectively under the irradiation of a specific wave band of AuNPs (at) SiO2, a strong local surface plasma resonance effect is generated, and a local electric field generated by resonance can enhance the thermal mobility of anions and cations in the gel, so that the Seebeck coefficient is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of flexible thermoelectric functional materials, and specifically relates to a preparation method and application of a light-gain flexible thermoelectric ion gel. Background Art

[0002] Low-grade waste heat is an abundant but often underutilized energy source in nature due to its low temperature gradient. Thermoelectric conversion technology based on the thermoelectric effect is an effective way to convert low-grade thermal energy into electrical energy. Thermoelectric materials are functional materials that use carriers (electrons, holes, and ions, etc.) to move in a directional manner under temperature differences to form continuous and stable output voltages and currents, thereby realizing direct conversion between thermal energy and electrical energy. Compared with electronic thermoelectric materials, ionic thermoelectric materials have a higher Seebeck coefficient. The current ionic thermoelectric material with the highest Seebeck coefficient reaches 34.5mV / k, but most ionic thermoelectric materials are made of ionic liquids, and their high price and toxicity limit their large-scale application and development.

[0003] Deep eutectic solvent (DES) is a new type of ionic liquid with the advantages of low cost, low volatility, biodegradability and high conductivity. Deep eutectic gel is a new type of ion gel with good conductivity and ductility, which has attracted much attention in the field of smart sensing and flexible electronics. However, the existing deep eutectic ion gel has a relatively single function, and its mechanical properties are not satisfactory due to the shielding effect of the solvent. In addition, the difference in thermal mobility between anions and cations is the key to improving the thermoelectric conversion rate. Under the illumination of a specific wavelength, noble metal nanoparticles have a surface plasmon resonance effect, which can generate a local electric field and promote ion migration. If the surface plasmon resonance effect combined with plasmon-metal nanoparticles can be developed to improve the thermoelectric technology for the thermal diffusion ion characteristics in ion gel, it will be of great significance to achieve high-performance ion thermoelectric gel. Based on the above status quo, it is still a huge challenge to prepare a deep eutectic solvent ion composite gel with long-term stability, self-healing, high conductivity, excellent mechanical properties and thermoelectric properties. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a light-gain flexible thermoelectric ion gel.

[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a light-gain flexible thermoelectric ion gel, characterized in that: it comprises:

[0008] preparing a deep eutectic solvent;

[0009] The deep eutectic solvent is mixed with anhydrous zinc chloride to form Zn-DES;

[0010] The light-gain flexible thermoelectric ion gel is obtained by uniformly mixing Zn-DES, acrylic acid, AuNPs@SiO2 and a photoinitiator and then polymerizing and curing them under UV conditions.

[0011] As a preferred embodiment of the preparation method of the present invention, the preparation method of the low eutectic solvent includes mixing a hydrogen bond donor and a hydrogen bond acceptor at 60-100° C. for 1-3 hours; wherein the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:3.

[0012] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the low eutectic solvent to anhydrous zinc chloride is 0.25 to 1.0.

[0013] As a preferred embodiment of the preparation method of the present invention, the mass ratio of Zn-DES, acrylic acid, AuNPs@SiO2 and photoinitiator is 46.3-65.2:13.3:1.2-4.8:10.

[0014] As a preferred embodiment of the preparation method of the present invention, the hydrogen bond acceptor includes one or more of choline chloride, anhydrous betaine, and methyltriphenylphosphonium bromide, and the hydrogen bond donor includes one or more of acrylic acid, 2-hydroxyethyl acrylate, itaconic acid, and citric acid.

[0015] As a preferred embodiment of the preparation method of the present invention, the particle size of the AuNPs@SiO2 is 15-25 nm, and the thickness of the silica shell is 5-8 nm.

[0016] As a preferred embodiment of the preparation method of the present invention, the photoinitiator includes one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoylphenyl ethyl phosphate, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0017] As a preferred embodiment of the preparation method of the present invention, the UV conditions are as follows: the UV light intensity is 10-120W, the UV band is 250-365nm, and the UV light irradiation time is 10-60s. Another object of the present invention is to overcome the deficiencies in the prior art and provide a light gain flexible thermoelectric ion gel prepared by a preparation method.

[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide applications of optical gain flexible thermoelectric ion gel in flexible intelligent sensors, energy generation and storage devices, actuators, transistors, electromagnetic shielding, touch screens and drug controlled release devices.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention proposes a new concept of light gain thermoelectric conversion technology based on low eutectic solvent ion gel. The innovation of this material lies in the ingenious introduction of AuNPs@SiO2 into PAA-Zn-DES ion gel, which achieves the effect of doubling the Seebeck coefficient under irradiation of a specific band (the generation of the Seebeck coefficient comes from the different diffusion speeds of anions and cations in the gel under temperature difference, resulting in a concentration difference in charge, and then generating voltage). The main reason for this multiple enhancement is that when AuNPs@SiO2 is irradiated in a specific band, the free electrons on the surface collectively oscillate, generating a strong local surface plasma resonance effect. The local electric field generated by the resonance can enhance the thermal mobility of anions and cations in the gel, thereby increasing the Seebeck coefficient.

[0021] (2) The present invention uses a new, designable zinc-based low eutectic solvent to prepare conductive ion gel, which not only overcomes the problems of poor ionic conductivity and toxicity of organic solvents, but also realizes multifunctional integration. It has good flexibility, high transparency, self-healing, excellent thermoelectric properties and mechanical properties. The advantages of being green, environmentally friendly, low-cost, easy to prepare and safe provide ideas for the preparation of more self-healing and good conductivity ion elastomer thermoelectric materials.

[0022] (3) The present invention is an ionic thermoelectric material whose carriers are anions and cations. The thermally diffused ions cannot directly pass into the electrodes and enter the external circuit, but can directly charge the capacitor. This provides a novel idea for realizing an "integrated" device - that is, simultaneously generating and storing electrical energy under an intermittent heat source. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0024] Figure 1 Schematic diagram of the preparation of PAA / ZnCl2DES thermoelectric ion gel and schematic diagram of the network microstructure of the embodiment of the present invention.

[0025] Figure 2 Schematic diagram of the thermoelectric performance of the PAA / ZnCl2 DES thermoelectric ion gel according to an embodiment of the present invention.

[0026] Figure 3 Schematic diagram of the thermal diffusion of optical gain of the PAA / ZnCl2DES thermoelectric ion gel according to an embodiment of the present invention. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.

[0031] Table 1

[0032]

[0033] Example 1

[0034] The present invention provides a method for preparing a zinc-based deep eutectic solvent ion gel:

[0035] (1) Preparation of Zn-DES: Choline chloride (ChCl) and 2-hydroxyethyl acrylate (HEA) were mixed in a molar ratio of 1:3 at 80°C and stirred at 300 r / min for 1 h until a colorless and transparent solution was formed. After cooling to room temperature, 0.63 g of anhydrous zinc chloride (the molar ratio relative to acrylic acid was 0.25) was added.

[0036] (2) Preparation of ion gel prepolymer solution: 6 g Zn-DES, 1.33 g acrylic acid and 0.1 g 1-hydroxycyclohexyl phenyl ketone were mixed evenly and stirred at room temperature for 1 h to obtain an ion gel prepolymer solution.

[0037] (3) Preparation of zinc-based low eutectic solvent ion gel: Pour the ion gel prepolymer obtained in step (2) into a polytetrafluoroethylene mold, place the mold under a 40W UV light source, and cure for 30 seconds to form an ion gel.

[0038] Example 2

[0039] The difference from Example 1 is that in step (1), Zn-DES is prepared by mixing choline chloride (ChCl) and 2-hydroxyethyl acrylate (HEA) in a molar ratio of 1:3 at 80°C and stirring at a speed of 300 r / min for 1 h until a colorless and transparent solution is formed. After cooling to room temperature, 1.26 g of anhydrous zinc chloride (the molar ratio relative to acrylic acid is 0.5) is added.

[0040] Example 3

[0041] The difference from Example 1 is that in step (1), Zn-DES is prepared by mixing choline chloride (ChCl) and 2-hydroxyethyl acrylate (HEA) in a molar ratio of 1:3 at 80°C and stirring at a speed of 300 r / min for 1 h until a colorless and transparent solution is formed. After cooling to room temperature, 1.89 g of anhydrous zinc chloride (the molar ratio relative to acrylic acid is 0.75) is added.

[0042] Example 4

[0043] The difference from Example 1 is that in step (1), Zn-DES is prepared by mixing choline chloride (ChCl) and 2-hydroxyethyl acrylate (HEA) in a molar ratio of 1:3 at 80°C and stirring at a speed of 300 r / min for 1 h until a colorless and transparent solution is formed. After cooling to room temperature, 2.52 g of anhydrous zinc chloride (the molar ratio relative to acrylic acid is 1.0) is added.

[0044] Example 5

[0045] The properties of the zinc-based deep eutectic solvent ion gel prepared in Examples 1-4 were tested. Mechanical properties test: The experiment was conducted according to the national standard GB / T1024.2-2006. The results are shown in Table 2.

[0046] Table 2 Properties of ion gels with different contents of anhydrous ZnCl2 added

[0047] Sample Breaking strength(MPa) Elongation at break (%) 1h self-repair rate (%) Example 1 5.77 1300 92.3 Example 2 8.14 1460 95.1 Example 3 9.72 1080 95.7 Example 4 12.04 410 96.5

[0048] Example 6

[0049] The present invention provides a method for preparing a light-gain flexible thermoelectric ion gel:

[0050] (1) Preparation of Zn-DES: Choline chloride (ChCl) and 2-hydroxyethyl acrylate (HEA) were mixed in a molar ratio of 1:3 at 80°C and stirred at 300 r / min for 1 h until a colorless and transparent solution was formed. After cooling to room temperature, 1.26 g of anhydrous zinc chloride (molar ratio relative to acrylic acid was 0.5) was added.

[0051] (2) Preparation of ion gel prepolymer mixed solution: 6 g Zn-DES, 1.33 g acrylic acid, 0.1 g 1-hydroxycyclohexyl phenyl ketone and 0.12 g AuNPs@SiO2 (2% of the total mass of Zn-DES) were mixed evenly and stirred at room temperature for 1 h to obtain an ion gel prepolymer mixed solution.

[0052] (3) Preparation of flexible thermoelectric ion gel: Pour the ion gel prepolymer obtained in step (2) into a polytetrafluoroethylene mold, place the mold under a 40W UV light source, and cure for 30 seconds to obtain a flexible thermoelectric ion gel.

[0053] Figure 1 The schematic diagram of the preparation of the thermoelectric ion gel and the schematic diagram of the network microstructure. During the polymerization process, AA and HEA can be used as hydrogen bond donors to form strong hydrogen bonds, and ChCl is used as a hydrogen bond acceptor. Compared with HEA, AA is more inclined to form intermolecular hydrogen bonds. The abundant hydrogen bond aggregation in the copolymer AA-ChCl makes it hard and brittle, while the copolymer HEA-ChCl tends to be soft and delicate; AuNPs@SiO2 reacts and combines with the polar groups in the ion gel, and the strong ionic bonds and multiple hydrogen bonding forces increase the mechanical strength of the ion gel; the addition of zinc ions improves the conductivity and mechanical properties of the ion gel.

[0054] Example 7

[0055] The difference from Example 6 is that step (2) prepares the ion gel prepolymer mixed solution: 6 g Zn-DES, 1.33 g acrylic acid, 0.1 g 1-hydroxycyclohexyl phenyl ketone and 0.36 g AuNPs@SiO2 (6% of the total mass of Zn-DES) are mixed evenly and stirred at room temperature for 1 h to obtain the ion gel prepolymer mixed solution.

[0056] Example 8

[0057] The difference from Example 6 is that step (2) prepares the ion gel prepolymer mixed solution: 6 g Zn-DES, 1.33 g acrylic acid, 0.1 g 1-hydroxycyclohexyl phenyl ketone and 0.48 g AuNPs@SiO2 (8% of the total mass of Zn-DES) are mixed evenly and stirred at room temperature for 1 h to obtain the ion gel prepolymer mixed solution.

[0058] Example 9

[0059] The performance of the optical gain flexible thermoelectric ion gel prepared in Examples 5-8 was tested.

[0060] (1) Seebeck coefficient test: Under 532nm illumination, the Seebeck coefficient of gel ions is measured by alternately adjusting the temperature between two electrodes in a planar and vertical configuration.

[0061] Figure 2 and Figure 3 The schematic diagrams of the thermoelectric performance and light gain thermal diffusion of the thermoelectric ion gel are shown respectively. When AuNPs@SiO2 is irradiated in a specific wavelength band, the free electrons on the surface collectively oscillate, producing a strong local surface plasmon resonance effect. The local electric field generated by the resonance can enhance the thermal mobility of anions and cations in the gel, thereby increasing the Seebeck coefficient.

[0062] (2) Conductivity test: All electrochemical tests were performed using a VSP-300 electrochemical workstation at ambient temperature. The conductivity of the sample was obtained by testing the electrochemical impedance spectrum of the sample in the range of 0.1 Hz to 1 MHz. Usually, a piece of ion gel was sandwiched between two copper sheets with an area of ​​0.5 cm 2 , thickness is 0.3 cm. The calculation formula (1) of ionic conductivity (σ) is as follows:

[0063] σ=I / (Rb*S) Formula (1),

[0064] Where:

[0065] σ——Electrical conductivity of hydrogel (mS / cm);

[0066] I——test thickness of hydrogel (cm);

[0067] Rb – body impedance, Ω, determined by the intersection of the impedance curve and the real axis;

[0068] S——test area of ​​hydrogel (cm 2 ).

[0069] (3) Self-healing test: The dumbbell-shaped ion gel was cut into two parts, one of which was stained with rhodamine B. The two cut parts were immediately removed and wrapped with sealing film and placed in an oven at 60°C for 1 h. The fracture stress before and after self-healing was tested using a universal testing machine to calculate the mechanical self-healing efficiency.

[0070] The results are shown in Table 3.

[0071] Table 3 Properties of ion gels with different contents of AuNPs@SiO2

[0072]

[0073] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a light-gain flexible thermoelectric ion gel, characterized in that: include, preparing a deep eutectic solvent; The deep eutectic solvent is mixed with anhydrous zinc chloride to form Zn-DES; The light-gain flexible thermoelectric ion gel is obtained by uniformly mixing Zn-DES, acrylic acid, AuNPs@SiO2 and a photoinitiator and polymerizing and curing them under UV conditions.

2. The preparation method according to claim 1, characterized in that: The preparation method of the low eutectic solvent comprises mixing a hydrogen bond donor and a hydrogen bond acceptor at 60 to 100° C. for 1 to 3 hours; wherein the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:

3.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the low eutectic solvent to anhydrous zinc chloride is 0.25 to 1.

0.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the Zn-DES, acrylic acid, AuNPs@SiO2 and the photoinitiator is 46.3-65.2:13.3:1.2-4.8:

10.

5. The preparation method according to claim 2, characterized in that: The hydrogen bond acceptor includes one or more of choline chloride, anhydrous betaine, and methyl triphenyl phosphonium bromide, and the hydrogen bond donor includes one or more of acrylic acid, 2-hydroxyethyl acrylate, itaconic acid, and citric acid.

6. The preparation method according to claim 4, characterized in that: The particle size of the AuNPs@SiO2 is 15-25 nm, and the thickness of the silicon dioxide shell is 5-8 nm.

7. The preparation method according to claim 4, characterized in that: The photoinitiator includes one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoylphenylethyl phosphate, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

8. The preparation method according to claim 7, characterized in that: The UV conditions are as follows: the irradiation intensity of the ultraviolet light is 10 to 120 W, the ultraviolet waveband is 250 to 365 nm, and the irradiation time of the ultraviolet light is 10 to 60 s.

9. The optical gain flexible thermoelectric ion gel prepared by the preparation method according to claims 1 to 8.

10. Application of the optical gain flexible thermoelectric ion gel as claimed in claim 9 in flexible intelligent sensors, energy generation and storage devices, actuators, transistors, electromagnetic shielding, touch screens and drug controlled release devices.

Citation Information

Patent Citations

  • Preparation method for flexible and transparent composite ionic liquid gel conductive electrode

    CN105140408A

  • Application of eutectic solvent in ionic gel, ionic gel and preparation method

    CN110054721A

  • Hydrogel electrode diaphragm suitable for being used as multi-channel physiological record processing system, and method

    CN112675318A

  • Self-healing stretchable eutectic gel electrolyte as well as preparation method and application thereof

    CN115548433A

  • Deep Eutectic Solvent Compositions

    US20200095400A1